The Impact of Metabolic Syndrome on the Risk for Disability Pension in Overweight and Obese Employees: A Prospective Study - Lidén, Edvard; Vihlborg, Per; Karlsson, Berndt; Torén, Kjell; Andersson, Eva (Journal of occupational and environmental medicine, 2025)
The aim of the study was to investigate the risk for disability pension in overweight and obese employees with or without metabolic syndrome. In a cohort based on occupational health data 1992-2009, the risk for any type of disability pension was analyzed with adjusted hazard ratios and 95% confidence intervals (CIs) both in normal weight, overweight, and obese employees and if the risk from metabolic syndrome was influenced by age and gender. Both overweight and obese employees had an increased risk for disability pension. Among employees with metabolic syndrome, hazard ratio was 1.89 (95% CI = 1.28-2.78) for young overweight men, 1.95 (95% CI = 1.03-3.69) for young obese men, and 2.26 (95% CI = 0.98-5.29) for young obese women. Metabolic syndrome increased the risk for disability pension in young male employees with overweight and obesity.